Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1007/s004210050466
|View full text |Cite
|
Sign up to set email alerts
|

Worsening of neck and shoulder complaints in humans are correlated with frequency parameters of electromyogram recorded 1-year earlier

Abstract: The aim was to investigate whether output and electromyogram (EMG) variables obtained from an isokinetic endurance test of the shoulder flexor muscles of 23 women with neck and shoulder problems in a car and truck industry correlated with improvement or worsening of complaints 1 year later. Each subject performed 100 maximal isokinetic shoulder forward flexions at 60 degrees x s(-1). Surface EMG of the trapezius, deltoid, biceps brachii and infraspinatus muscles and mechanical output (peak torque) were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…This assumption was con®rmed in the present study; subjects with a high proportion of type 1 muscle ®bres had more diculty in relaxing during the passive parts of the contraction cycle than subjects with a high proportion of type 2 muscle ®bres. In agreement with the present ®ndings and interpretations, we have recently found that a high SAR in the shoulder muscles was correlated with worsening in complaints from the neck and shoulders 1 year later (Lundblad et al 1998). The present observation of a correlation between SAR and the proportion of type 1 muscle ®bres is also interesting since studies of the trapezius muscle in clinically healthy subjects and subjects with work-related myalgia indicate that it is mainly the type 1 ®bres that are aected in work-related myalgia (i.e.…”
Section: Sarsupporting
confidence: 79%
See 1 more Smart Citation
“…This assumption was con®rmed in the present study; subjects with a high proportion of type 1 muscle ®bres had more diculty in relaxing during the passive parts of the contraction cycle than subjects with a high proportion of type 2 muscle ®bres. In agreement with the present ®ndings and interpretations, we have recently found that a high SAR in the shoulder muscles was correlated with worsening in complaints from the neck and shoulders 1 year later (Lundblad et al 1998). The present observation of a correlation between SAR and the proportion of type 1 muscle ®bres is also interesting since studies of the trapezius muscle in clinically healthy subjects and subjects with work-related myalgia indicate that it is mainly the type 1 ®bres that are aected in work-related myalgia (i.e.…”
Section: Sarsupporting
confidence: 79%
“…An initial steep decrease (during the initial 40±60 contractions) in force output and mean frequency (MNF) of the EMG (the fatigue phase) followed by a plateau (the endurance level) with no further decrease occurs during repetitive maximum dynamic (isokinetic) contractions (for references see LindstroÈ m et al 1997;Lundblad et al 1998). The reported behaviour of the signal amplitude [root mean square, RMS or integrated (i) EMG] of the EMG during the fatigue phase are heterogeneous (both increases and decreases have been reported), according to the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Shifts towards lower spectral frequencies during a sustained contraction -an indirect indicator of changes in membrane properties -may reflect local muscle fatigue (Merletti et al, 1990;De Luca, 1997). However, little is known about the effects of muscle pain on local EMG frequency shift, and existing results are not clear: increased shift (Gogia and Sabbahi, 1994;Falla et al, 2003) and less frequency shift have both been reported (Lundblad et al, 1998;Kallenberg et al, 2006). Less neck-flexor frequency shift has also been indicated in helicopter pilots with frequent neck pain (Ang et al, 2005).…”
Section: Introductionmentioning
confidence: 93%
“…The ®rst component of Table 5 shows that the prevalence of RR ®bres correlated positively with MNFer of the trapezius, infraspinatus, and deltoid muscles (and with SARe of the deltoid muscle). The shift of MNF has been reported to indicate peripheral muscle fatigue during sustained static contractions (Basmajian and DeLuca 1985) and in some studies prominent shifts have been suggested to re¯ect an increased risk of work-related myalgia (for references see Lundblad et al 1998). In contrast to this suggestion, a prospective study of female workers reported that small MNF shifts (high MNFer) of the shoulder¯exor muscles were associated with an increased risk of worsening the complaints of pain in the neck and shoulders 1 year later (Lundblad et al1998).…”
Section: Multivariate Relationshipsmentioning
confidence: 99%